PENGARUH BELANJA MODAL PEMERINTAH DAERAH DAN INVESTASI SWASTA TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - B01110069, RIDUAN (Jurnal Pembangunan dan Pemerataan, 2015)
This thesis titled "The Effect of Local Government Capital Expenditure and Private Investment on Growth Economic And Social Welfare District / Municipality in the Province of West Kalimantan". With the aim 1. Examine and analyze the effect of capital expenditure to economic growth in the district / city in the province of West Kalimantan, 2. Examine and analyze the effect of private investment to economic growth in the district / city in the province of West Kalimantan, 3. Examine and analyze the influence of economic growth on the welfare of the community in the district / city in the province of West Kalimantan. The method used in this research is quantitative descriptive by using secondary data. processed by using a computer software program economics views (E-views). using the fixed effect panel method Least Square (PLS) The results of the study concluded that capital expenditure has no significant effect on economic growth, it is because the cost of construction insfratruktur large, less productive allocation of funds and the possibility of leaks. Private investment has no significant effect on economic growth because it takes a long time to be able to support economic growth and economic growth has a significant influence on the welfare of the community, because a lot of economic growth driven by the tertiary sector is relatively well wellbeing. Keywords: Economic Growth, Capital Expenditure, Private Investment, Public Welfare (IPM)